2019
DOI: 10.2967/jnumed.118.225599
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Time-Point 18F-Fluorocholine PET/CT in Parathyroid Imaging

Abstract: 18 F-fluorocholine ( 18 F-FCH) PET/CT is a promising and increasingly used scan technique in the preoperative imaging of parathyroid adenoma. Several acquisition methods have been evaluated in the literature, but the optimal image acquisition time point after administration of the tracer is still under debate. Methods: Patients who had hyperparathyroidism, underwent dual-time-point 18 F-FCH PET/ CT (image acquisition, 5 min; 60 min after injection), and had histologically proven pathologic parathyroid glands w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Another limitation is that, because of the short half-life of 11 C, late imaging was not feasible in our study. A combination of early and delayed imaging was recently shown to detect additional PTAs using 18 F-fluorocholine PET/CT in a large collective of 64 patients (28). A direct comparison cannot be made because of differences in the patient collective and study setup; however, even when the inconclusive cases are included, the ratio of parathyroid to normal thyroid tissue in our study appears to be at least as high as the ratio in the above-mentioned study (28).…”
Section: Discussionmentioning
confidence: 48%
“…Another limitation is that, because of the short half-life of 11 C, late imaging was not feasible in our study. A combination of early and delayed imaging was recently shown to detect additional PTAs using 18 F-fluorocholine PET/CT in a large collective of 64 patients (28). A direct comparison cannot be made because of differences in the patient collective and study setup; however, even when the inconclusive cases are included, the ratio of parathyroid to normal thyroid tissue in our study appears to be at least as high as the ratio in the above-mentioned study (28).…”
Section: Discussionmentioning
confidence: 48%
“…Four pathologic parathyroids (two patients) were not detected by the three imaging modalities probably due to their small size and weight (less than 10 mm and 0.1 g), an uncommon histological characteristic (one case of oncocytic micro-adenoma), and patient biological profiles (slight PTH increase (83 pg/mL) and subnormal calcemia (2.60 mmol/L) in one case, and moderate PTH increase (102 pg/mL) and vitamin D insufficiency (21 ng/mL) in the other one). Interestingly, some recent evidence points out the potential of a PET dual-time-point acquisition protocol to reduce false negative results in cases of negative/inconclusive standard PET study [ 27 ]. As previously reported [ 28 , 29 ], we found a positive and significant correlation between blood PTH level, parathyroid gland weight, and both SUVmax and MTV.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing early and delayed static acquisitions, several authors observed a better lesion-to-background and lesion-to-thyroid contrast on late images but all lesions were visible at both phases [16,17,21,31].…”
Section: Semi-quantitative Analysis and Biochemical Data Correlationmentioning
confidence: 99%
“…In the setting of benign lesions, dual time scanning can help with a differential diagnosis; in the late phase, choline uptake decreases both in the thyroid gland parenchyma and inflammatory lymph nodes whereas it increases in parathyroid adenomas [25,26,31]. Similarly, Prabhu et al reported that early dynamic imaging could also be helpful in differentiating between parathyroid adenomas and cervical reactive lymph nodes that might be confused with small adenomas/hyperplasic glands.…”
Section: Pitfallsmentioning
confidence: 99%